Selective and Sensitive Detection of Cyanide Based on the Displacement Strategy Using a Water-Soluble Fluorescent Probe - Ming La; Yuanqiang Hao; Zhaoyang Wang; Guo-Cheng Han; Lingbo Qu (Journal of Analytical Methods in Chemistry)
A water-soluble fluorescent probe (C-GGH) was used for the highly sensitive and selective detection of cyanide (CN−) in aqueous media based on the displacement strategy. Due to the presence of the recognition unit GGH (Gly-Gly-His), the probe C-GGH can coordinate with Cu2+ and consequently display ON-OFF type fluorescence response. Furthermore, the in situ formed nonfluorescent C-GGH-Cu2+ complex can act as an effective OFF-ON type fluorescent probe for sensing CN− anion. Due to the strong binding affinity of CN− to Cu2+, CN− can extract Cu2+ from C-GGH-Cu2+ complex, leading to the release of C-GGH and the recovery of fluorescent emission of the system. The probe C-GGH-Cu2+ allowed detection of CN− in aqueous solution with a LOD (limit of detection) of 0.017 μmol/L which is much lower than the maximum contaminant level (1.9 μmol/L) for CN− in drinking water set by the WHO (World Health Organization). The probe also displayed excellent specificity for CN− towards other anions, including F−, Cl−, Br−, I−, SCN−, PO43-, N3-, NO3-, AcO−, SO42-, and CO32-.